Virtual power plant using demand response management - Teo, Jonathan Chin Hao (2015)
This Final Year Report serves to provide a bird-view on how a virtual power plant is built in my perspective and focuses more on the automation of load shedding via demand response management. A virtual power plant (VPP) will be developed using demand response management system that will interface with a number of building energy management systems (BEMS) to facilitate load control and short-term load reduction at the consumer premises during system constraints or period of maximum demand. In this way, the VPP will impose demand limits to participating consumers in response to supply conditions and in response to market prices. The BEMS will help keep the building grid in balance when energy supplies get tight, or as more distribution generations like solar, wind, and micro-turbine come online.